2019
DOI: 10.1111/psyp.13383
|View full text |Cite
|
Sign up to set email alerts
|

Target‐related parietal P3 and medial frontal theta index the genetic risk for problematic substance use

Abstract: Theoretical and empirical work suggests that problematic substance use (PSU) is associated with individual differences in prefrontal cortex activity. While research has strongly linked parietal P3 amplitude reduction (P3AR) to genetic risk for problematic substance use, few studies have tested whether prefrontal EEG measures are sensitive to this genetic liability. In addition to P3, oddball target detection tasks elicit medial frontal theta power, reflecting attentional allocation, and parietal delta, indexin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 122 publications
(241 reference statements)
1
10
0
Order By: Relevance
“…Future longitudinal research is necessary to examine the potential feedback loops that might exist between theta-related neural changes and alcohol abuse. Reduced FM power may share genetic influences with problematic substance use in general (111). This study also identified a strong genetic relationship between FM power and inconsistency in responding (RTV), confirming an earlier study in ADHD (19).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
“…Future longitudinal research is necessary to examine the potential feedback loops that might exist between theta-related neural changes and alcohol abuse. Reduced FM power may share genetic influences with problematic substance use in general (111). This study also identified a strong genetic relationship between FM power and inconsistency in responding (RTV), confirming an earlier study in ADHD (19).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
“…These findings provide important evidence supporting the endophenotypic construct validity of midfrontal target-related theta (Iacono et al ., 2017). Theta is associated with normative and pathological alcohol use (Jones et al ., 2006; Andrew and Fein, 2010; Yoon et al ., 2013; Harper et al ., 2019); heritable (Harper et al ., 2019); diminished in first-degree relatives with AUD (Rangaswamy et al ., 2007); shares genetic variance with alcohol use (Harper et al ., 2019); and predicts alcohol use development (as shown here); all of which are important criterion for an endophenotype (Gottesman and Gould, 2003; Iacono et al ., 2017). Midfrontal theta elicited by other experimental tasks and cognitive processes, such as inhibitory control (Kamarajan et al ., 2006; however, see Harper et al ., 2018 b ), response conflict (Harper et al ., 2017 a , 2018 a ), and feedback processing (Kamarajan et al ., 2015) may also reflect candidate endophenotypes for clinical and non-clinical drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous 61-channel EEG was collected at age-14 and processed as described in our previous reports (Harper et al ., 2017 b , 2019) (see online Supplementary Material).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P3 amplitude reduction is reliably associated with schizophrenia and several forms of substance use, including alcohol, nicotine, and cannabis ( Anokhin et al 2000 ; Bramon, Rabe-Hesketh, Sham, Murray, & Frangou, 2004 ; Euser et al 2012 ; Iacono & Malone, 2011 ; Iacono et al 2017 ; Solowij, Michie, & Fox, 1991 ). Reduced θ and δ energies and ITPC are also associated with substance use and schizophrenia ( Burwell, Malone, Bernat, & Iacono, 2014 ; Ethridge et al 2015 , 2012 ; Ford, Roach, Hoffman, & Mathalon, 2008 ; Harper, Malone, & Iacono, 2019b ; Jones et al 2006 ; Rangaswamy et al 2007 ; Yoon, Malone, Burwell, Bernat, & Iacono, 2013 ).…”
Section: Methodsmentioning
confidence: 99%